Management of recalcitrant ulcer in elderly patients with anemia: A case report - Marlina, Erni; Usman, Nur A.; Rahayu, Masita (Hasanuddin University, 2022)
Objective: This case report aimed to answer challenging in the treatment of chronic recalcitrant ulcers in elderly complicated by anemic condition. A 68 years old female patient came to Hasanuddin University Dental Hospital with chief complaint of recalcitrant painful canker sores affecting mouth and throat.Methods: Elder age could contribute in difficulty swallowing due to reduced saliva, slow eating habit, lost or caries teeth which lead to a less efficiency in the absorption of important nutrients such as iron and folic acid. This condition triggers a recalcitrant but chronic ulcer which in the end would add more difficulties for swallowing. A part from the pale conjunctiva of the eye, there was no other abnormality found extra orally. Drug therapy Bcom 150 mg with chlorhexidine gluconate 0.2% mouthwash and systemic corticosteroid.Results: Blood screening results demonstrated lower hemoglobin level with 11.6 and hematocrit 35.6 with referred value of 12 and 37, respectively. Long visit was needed to slowly adapted patient oral environment with local condition, as well as from systemic background improvement. Recalcitrant but chronic ulcers might be challenging in the treatment due to variabilities contributed factors such as age, unhealthy-eating habits, systemic background, and local oral hygiene and condition. One should be careful and be patient in changing the long behavior of the patient.Conclusion: Most importantly, patient been given advice to change her eating behaviors by consume more iron and folic acid food, and avoid irritant food. Local irritant of element 45 also been grinded.